The Relationship between Students’ Motivation to Learn and Teachers’ Self-efficacy in Mathematics among Secondary School Students in Kenya - Ngunjiri, Mbuthia; Singh, P. N. (JOURNAL OF INDIAN EDUCATION, 2012)
This study focuses on the relationship between students' motivation to learn and teachers' self-efficacy in mathematics. It was found that there is a significant gender difference in motivation to learn mathematics, favouring males. Students' motivation to learn did not differ significantly with respect to locality. Teachers' self-efficacy in mathematics significantly contributed to the prediction of motivation to learn mathematics. Mathematics teachers should enhance students' motivation to learn especially for females. Teachers and educators should place emphasis on awareness of sources and enhancement strategies of teachers' sense of efficacy for students' success in mathematics.